Production of coconut shell liquid smoke from pilot plant of pyrolysis process - Mohd Yusoff, Nur Sakinah; Mel, Maizirwan; Wan Bazli, Wan Ishak; Azmi, Azlin Suhaida (Akademia Baru, 2017)
Liquid smoking in preserving protein-based foods such as meat, fish and cheese has been increasingly utilized, giving a pleasant flavour and inhibit the effects of pathogens. Liquid smoke is the product of pyrolysis system and distillation process. The smoke produced by incomplete combustion reaction involves the decomposition of polymers into low molecular weight of organic compound due to the effect of oxidation reaction, polymerization and condensation. Coconut Shell Liquid Smoke (CSLS) has been reported to be safe and not toxic to animals and human health. In this study, coconut shells are used to produce the liquid smoke using pyrolysis and condensation processes. The main objective of this research is to produce liquid smoke from coconut shell using 230 L pilot plant of pyrolysis system. The process conditions and characteristics for high yield of coconut shell liquid smoke production were determined. The composition and characteristics of coconut shell liquid smoke was also analysed. Result shows that the pyrolysis of coconut shell using the designed system produced the highest liquid smoke yield of 36.93 wt% obtained from run 1 at reaction temperature of 220o C in five hours.